Dejerine-Roussy syndrome from thalamic metastasis treated with stereotactic radiosurgery. (October 2017) - Patel, Rajal A.; Chandler, James P.; Jain, Sarika; Gopalakrishnan, Mahesh; Sachdev, Sean
Highlights: Dejerine-Roussy syndrome is associated with damage to the thalamus. Stereotactic radiosurgery was utilized to treat a thalamic metastasis. Radiosurgery to the thalamic metastasis alone can alleviate a pain syndrome. Abstract: Dejerine-Roussy syndrome (central thalamic pain) is associated with damage to the ventral posterior sensory nuclei of the thalamus. We report a patient with breast cancer who developed contralateral hemibody paresthesias and dysesthesias. MR imaging revealed limited volume intracranial metastatic disease including a right posterior thalamic lesion. Stereotactic radiosurgery was utilized to selectively treat the lesion while preserving the remaining thalamus. Two months following treatment, the patient reported vastly improved to complete resolution of her sensory symptoms. This is the first reported case of thalamic tumor directed radiosurgical treatment leading to resolution of central neuropathic pain.